Pengukuran Stating Point Dimensi Strategi Inovasi Studi Pada Pusat Pengembangan Sumber Daya Manusia Aparatur Esdm - Hendris Agung Prasojo; Dian Anggarini (JURNAL APARATUR, 2021)
ABSTRACTThe Center for Human Resources development for the ESDM Apparatus is a training institution that provides soft skills and hard skills training, so that PPSDMA can act as an example for other institutions within the Ministry of Energy and Mineral Resources. PPSDMA can adapt to ongoing changes, because it demands continuous innovation so that the organization can be sustainable. The purpose of this research is that PPSDMA can find out the current position of innovation, by measuring the organizational innovation stating point. This study classifies the dimensions and levels of innovation at PPSDMA, Ministry of Energy and Mineral Resources. Each dimension was measured using a questionnaire to employees at PPSDMA. The results of the measurement of the eight innovation strategies are processed quantitatively and statistically and the minimum score is 2.54 and the maximum score is 3. 09. The average score obtained is 2.83 is a sufficient score, which is in the middle position so that PPSDMA is at the stating point as a hopeful innovator. PPSDMA has a spirit of innovation, even though the organization is inclined towards gradual improvement rather than making innovations that change internal business process patterns. Likewise, the organizational approach is still ad hoc and unstructured. PPSDMA should take a systematic view of the core strategic, customer-focused, and focus on the organizational factors needed for the innovation strategy and immediately look for "get it first" opportunities. Take the time to incorporate organizational learning and begin to define processes for continuous innovation. ABSTRAKPusat pengembangan Sumber Daya Manusia Aparatur ESDM merupakan Lembaga pelatihan yang memberikan pelatihan soft skill dan hard skill, sehingga PPSDMA dapat berlaku sebagai contoh bagi institusi lain di lingkungan kementerian ESDM. PPSDMA dapat berdapatasi dengan perubahan yang terus terjadi, karena itu menuntut inovasi yang terus menerus  agar organisasi dapat berkelanjutan. Tujuan penelitian ini agar PPSDMA dapat mengetahui posisi inovasi saat ini, melalui pengukuran stating point inovasi organisasi. Penelitian ini mengelompokan dimensi dan tingkat inovasi di PPSDMA, Kementerian Energi dan Sumber Daya Mineral. Masing masing dimensi diukur dengan menggunakan quesioner terhadap pegawai di PPSDMA. Hasil pengukuran delapan strategi inovasi, diolah secara kuatitatif dan statistic dan didapat skor minimal diangka 2.54 dan maksimal 3. 09. Skor rata rata yang didapat 2.83 merupakan skor cukup, yaitu di posisi tengah sehingga PPSDMA ada pada stating point sebagai hopeful innovator. PPSDMA memiliki semangat inovasi, meskipun organisasi condong ke perbaikan bertahap daripada melakukan  inovasi yang mengubah pola internal business process. Begitu pula, pendekatan organisasi masih bersifat ad hoc dan tidak terstruktur. PPSDMA sebaiknya mengambil pandangan sistematis dari strategis inti, fokus pada pelanggan, dan fokus pada faktor organisasi yang diperlukan, untuk strategi inovasi dan segera mencari peluang "capai yang mudah lebih dulu". Luangkan waktu untuk memasukkan pembelajaran organisasi dan mulai menentukan proses untuk inovasi yang berkelanjutan.